Eco-humanism and Democratic Culture in the Transformation of Education for the Wellbeing of Engineering Students - Sri, S.Snekha; K, Rajitha; Muraleedharan, Divya; K, Premkishor S; Elakkia. R, Tamil; Prabhakaran, S. (Journal of Ecohumanism, 2025)
This study explores the transformative role of AI-driven applications in engineering education and their impact on student wellbeing. With the rapid advancement of emerging technologies, there is an urgent need to understand how AI can enhance educational outcomes while promoting holistic development among engineering students. Utilizing a mixed-methods approach, this research combines quantitative surveys and qualitative interviews to assess the effectiveness of AI tools, including intelligent tutoring systems and adaptive learning technologies. The findings reveal that AI applications significantly improve learning outcomes and enhance student wellbeing by providing personalized learning paths, reducing cognitive load, and fostering engagement with educational materials. Furthermore, adaptive technologies support emotional resilience and a sense of belonging, which are critical for student success. This research emphasizes the importance of integrating AI with student-centric pedagogical strategies to create a more adaptive and supportive educational environment, ultimately contributing to sustainable transformations in engineering education.